A study of metaphoric and metonymic expressions of body part terms hand and head in Hausa / Yusuf Ahmed Gwarzo - Gwarzo, Yusuf Ahmed (2015)

(untitled)
Numerous studies have been conducted on metaphor and metonymy on body part terms across the languages. Within the conceptual metaphor and metonymy theory of Lakoff and Johnson (1980), Lakoff (1987), Radden and Kövecses (1999) and Radeen and Dirven (2007), the present research investigates the conceptualizations of body part terms in Hausa language. The research only investigates the conceptualizations of hannu ‘hand’ and kai ‘head’ in the Hausa language. The study is aimed at identifying the metaphorical and metonymical expressions of both hannu ‘hand’ and kai ‘head’ in the Hausa language. The study also examines how the idealized cognitive models (ICMs) are operating for the creations of hannu ‘hand’ and kai ‘head’ metaphors and metonymies. The Analysis of the investigation found that metaphorically hannu ‘hand’ is conceptualized as HAND IS CONTROL, HAND IS POSSESSION, HAND IS ATTENTION and HAND IS COOPERATION. Metonymically, hannu ‘hand’ is conceptualized as HAND STANDS FOR ACTIVITY, HAND STANDS FOR PERSON, HAND STANDS FOR SKILL, HAND STANDS FOR CONTROL, HAND STANDS FOR PERSONALITY, HAND STANDS FOR SIDE and HAND STANDS FOR GIVEN. The analysis further found that the metaphorical expressions of kai ‘head’ as HEAD IS A CONTAINER OF INTELLIGENCE, HEAD AS A TOP OF THING, HEAD AS A TIP OF THING, HEAD AS BEGINNING OF THING, HEAD AS MOVING OBJECT, HEAD AS INDEPENDENCE OF AN OBJECT and HEAD AS SUFFICE OF AN OBJECT. Metonymical expressions of kai ‘head’ identified include HEAD STANDS FOR PERSON, HEAD STANDS FOR INTELLIGENCE, HEAD STANDS FOR INDEPENDENCE, HEAD STANDS FOR COOPERATION, HEAD STANDS FOR LENGTH and HEAD STANDS FOR AGREEMENT. Analysis also revealed that the containment ICM, human being ICM, non-human ICM, and part-whole ICM are ICMs that are involved in the creation of the metaphorical and metonymical expressions of hannu ‘hand’ and kai ‘head’ in the Hausa language. The findings revealed that the speakers of Hausa language make use of body part terms hannu ‘hand’ and kai ‘head’ to evoked figurative conceptualizations and both hannu ‘hand’ and kai ‘head’ plays a significant role in Hausa language and culture, describing various activities, functions and the human experience. The findings also revealed that the conceptualizations of both hannu ‘hand’ and kai ‘head’ were as a result of their general function in the human body and some time specific cultural beliefs that have root in the language traditions.